Ethical Issues of Publication of Research Results - Yu. A. Gryzunov; A. M. Golubev; I. O. Zaks (Общая реаниматология, 2007)
The paper summarizes the principles of ethics of scientific publications. These principles have been elaborated on the basis of the «Uniform Requirements for Papers Submitted to Biomedical Journals» of the International Committee of Editors of Medical Periodicals. They should be kept in mind when developing the strategy of scientific journals. Each journal should adopt a high profile that readers, authors, and reviewers should familiarize with.